Financial development and employment: Evidence from transition countries - Dorothea Schäfer; Susan Steiner (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
This paper studies the association between a country's level of financial development and firms' employment growth. We employ an incomplete contract model for evaluating this association. The model proposes that a high level of financial development affects the employment of firms with low managerial capital negatively, while firms with high managerial capital benefit from a more developed financial system. We test this proposition with data from the Business Environment and Enterprise Performance Survey covering transition countries in Eastern Europe and Central Asia. We use firm size as a proxy for managerial capital. Our findings confirm a non-linear effect of financial development on firm employment. Specifically, the smallest firms' edge in employment growth over large firms is dampened when the level of financial development is higher, especially in countries at medium levels of financial development.
Keywords: G20; G28; G30; J30; 330; Financial Development; Employment; Financial Constraints; Transition